2014
DOI: 10.4049/jimmunol.1303125
|View full text |Cite
|
Sign up to set email alerts
|

CD20+ B Cell Depletion Alters T Cell Homing

Abstract: Depleting mAbs against the pan B cell marker CD20 are remarkably effective in the treatment of autoimmune-mediated inflammatory disorders, but the underlying mechanisms are poorly defined. The primary objective of this study was to find a mechanistic explanation for the remarkable clinical effect of the anti-CD20 mAbs in a representative nonhuman primate autoimmune-mediated inflammatory disorder model, experimental autoimmune encephalomyelitis (EAE) in common marmosets, allowing detailed analysis of secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…19,[45][46][47] RTX-induced B cell depletion could actually modify antigen presentation and cytokine production 45 as well as alteration of T cell homeostasis and homing. 48 Our results showed that total T cells were not affected by RTX, and whereas CD4 + /CD8 + T cell ratio increased after RTX treatment, there was no difference between relapsers and nonrelapsers in the T cell subsets.…”
Section: Discussionmentioning
confidence: 43%
“…19,[45][46][47] RTX-induced B cell depletion could actually modify antigen presentation and cytokine production 45 as well as alteration of T cell homeostasis and homing. 48 Our results showed that total T cells were not affected by RTX, and whereas CD4 + /CD8 + T cell ratio increased after RTX treatment, there was no difference between relapsers and nonrelapsers in the T cell subsets.…”
Section: Discussionmentioning
confidence: 43%
“…Previous findings hint at a role for the IL-7 signaling pathway in EAE developing in marmosets immunized with recombinant human myelin oligodendrocyte glycoprotein (rhMOG)/CFA. Depletion of CD20 + B cells in the marmoset EAE model inhibits the activation and lymph node emigration of T cells and consequently prevents the development of clinical symptoms and pathology (Jagessar et al 2012;Kap et al 2010;Kap et al 2014). In B-cell depleted marmosets, CD127 expression on T cells was not down-regulated, but IL-7 mRNA levels were profoundly suppressed (Kap et al 2014).…”
mentioning
confidence: 93%
“…Depletion of CD20 + B cells in the marmoset EAE model inhibits the activation and lymph node emigration of T cells and consequently prevents the development of clinical symptoms and pathology (Jagessar et al 2012;Kap et al 2010;Kap et al 2014). In B-cell depleted marmosets, CD127 expression on T cells was not down-regulated, but IL-7 mRNA levels were profoundly suppressed (Kap et al 2014). In addition, in B-cell depleted marmosets the viral load of CalHV3, which is the marmoset lymphocryptovirus equivalent of EpsteinBarr virus (EBV), was reduced (Jagessar et al 2013a).…”
mentioning
confidence: 93%
“…We observed that the space left inside lymph nodes by the depletion of CD20+ ve B cells is replenished by activated T cells expressing the lymph node homing receptor CCR7. This was not observed in monkeys treated with anti-BlyS or anti-APRIL mAb (Kap et al, 2014). This finding may suggest that the anti-CD20 treatment may interfere with the licensing of activated autoreactive T cells to egress the lymph nodes.…”
Section: Treatments Targeting B Cellsmentioning
confidence: 85%